Assessment of Living Room Furniture Arrangement on Wellbeing Case Study Jeddah Residents, Saudi Arabia - Makkawi, Fattwo Abdul Rahman; Md. Yusoff, Irwan Syah; Che Me, Rosalam (Advances in Social Sciences Research Journal, 2024)
This review explores the impact of living room furniture arrangement on the wellbeing of residents in Jeddah, integrating cultural, environmental, and psychological perspectives. It synthesizes findings from various qualitative studies, highlighting the significant role of cultural and traditional elements in living space design. The review emphasizes the importance of biophilic design, adaptability, and flexibility in modern living spaces, particularly in the context of post-COVID-19 lifestyle changes. It also examines the influence of urban planning and socio-economic factors on residential space design and its impact on resident wellbeing. Key conclusions suggest that living room arrangements in Jeddah should resonate with cultural values, incorporate biophilic elements, and be adaptable to multifunctional use. Future research directions include further exploration of cultural aspects in living space design, innovations in biophilic integration, adaptive design solutions, and the establishment of wellbeing metrics for evidence-based design. The review acknowledges limitations in scope, potential biases, and the dynamic nature of urban living, underscoring the need for ongoing research.